2014
DOI: 10.1111/bph.12830
|View full text |Cite
|
Sign up to set email alerts
|

Conformational flexibility of the agonist binding jaw of the human P2X3 receptor is a prerequisite for channel opening

Abstract: BACKGROUND AND PURPOSEIt is assumed that ATP induces closure of the binding jaw of ligand-gated P2X receptors, which eventually results in the opening of the membrane channel and the flux of cations. Immobilization by cysteine mutagenesis of the binding jaw inhibited ATP-induced current responses, but did not allow discrimination between disturbances of binding, gating, subunit assembly or trafficking to the plasma membrane. EXPERIMENTAL APPROACHA molecular model of the pain-relevant human (h)P2X3 receptor was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 51 publications
(88 reference statements)
2
24
0
Order By: Relevance
“…1A) (16,17). It has been demonstrated that channel activation was associated with the downward motion of the head domain that is coordinated with ATP binding (20,25). As revealed in MD simulations, we observed alterations of movement in the head domain after losing this salt bridge (Figs.…”
Section: Discussionsupporting
confidence: 53%
“…1A) (16,17). It has been demonstrated that channel activation was associated with the downward motion of the head domain that is coordinated with ATP binding (20,25). As revealed in MD simulations, we observed alterations of movement in the head domain after losing this salt bridge (Figs.…”
Section: Discussionsupporting
confidence: 53%
“…Although the sequence of the head domain is not highly www.nature.com/aps Wang J et al Acta Pharmacologica Sinica npg conserved throughout the P2X family, the architecture of this domain in different subtypes shares certain similarity due to three conserved disulfide bonds that contribute to the folding of P2X receptors [38][39][40][41][42] (Figure 2A and 2C). The architecture of head domain of the zfP2X4 receptor was determined by X-ray diffraction and showed a high similarity in folding pattern with rat P2X4 (rP2X4) resolved by nuclear magnetic resonance, suggesting the conservation of the P2X4 head domain in different species [40] .…”
Section: Head Domainmentioning
confidence: 99%
“…In the hP2X3R, we have recently shown by disulfide trapping analysis that the conformational mobility of domains constituting the inter-subunit ATP-binding site is essential for ATP-induced channel opening [21]. By using homology modeling and functional analysis of alanine mutants, the residues K63, K65, T172, K176, N279, F280, R281, and K299 of the hP2X3R were identified to be important for ATP-binding [22].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…In a preceding paper, we simulated molecular dynamics of the hP2X3R, based upon its closed homology model, and thereby identified regions of the receptor ectodomain approaching each other around the agonist binding pocket [21]. Then, we generated potential cysteine double mutants in order to check the possibility of disulfide bond formation and subsequent immobilization/inactivation of the receptor.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation